2021
DOI: 10.3390/molecules26154503
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Structure and Impact of 5-Aminoorotic Acid and Its Complexes with Lanthanum(III) and Gallium(III) on the Activity of Xanthine Oxidase

Abstract: The superoxide radical ion is involved in numerous physiological processes, associated with both health and pathology. Its participation in cancer onset and progression is well documented. Lanthanum(III) and gallium(III) are cations that are known to possess anticancer properties. Their coordination complexes are being investigated by the scientific community in the search for novel oncological disease remedies. Their complexes with 5-aminoorotic acid suppress superoxide, derived enzymatically from xanthine/xa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 99 publications
1
5
0
Order By: Relevance
“…The cytotoxicity of Ga ions is well known. These results confirmed our previous observations on the cytotoxicity of Ga(III) complexes with other biologically active ligands [48][49][50].…”
Section: Pharmacologysupporting
confidence: 92%
“…The cytotoxicity of Ga ions is well known. These results confirmed our previous observations on the cytotoxicity of Ga(III) complexes with other biologically active ligands [48][49][50].…”
Section: Pharmacologysupporting
confidence: 92%
“…Recently, compounds 8 – 11 with antioxidant activity against AD have been reported (Figure 2). [26–29] …”
Section: Introductionmentioning
confidence: 99%
“…Recently, several studies have newly found that both anti-inflammatory drugs (such as ibuprofen) and 5-aminoorotic acid could serve as new inhibitors to xanthine oxidase. 24 , 25 However, over the past few decades, the progress in drug research to treat gout was slow. Moreover, the traditional treatment mainly focuses on the control of the clinical manifestation – high level of inflammation, but pays little attention to the immune disorders related to the pathogenesis of AGA.…”
Section: Introductionmentioning
confidence: 99%